Reaksi Pasar Atas Pengumuman Kenaikan Bank Indonesia 7-Day Reserve Repo Rate Tanggal 19 Oktober 2023 - Cahyani, Ni Luh Pipin; Wirakusuma, Made Gede (Fakultas Ekonomi Universitas Samudra, 2025)
In the capital market, investors are very attentive to the information content of an event, one of which is the event of an increase in the Bank Indonesia 7-day reserve repo rate (BI7DRR). This event caused a decrease in the IDX Composite, followed by a decline in stock prices. The purpose of this study is to examine how the capital market reacted to the announcement of the increase in the BI7DRR on October 19, 2023, using abnormal returns and trading volume activity as proxies. Total of 79 companies in the property and real estate sectors was taken using purposive sampling method and ypothesis testing was conducted using the nonparametric Wilcoxon signed-rank test. The results show that there is a difference in abnormal returns before and after the increase in BI7DRR, but there is no difference in trading volume activity before and after the increase in BI7DRR.